An urban intertidal reef is dominated by fleshy macroalgae, sediment, and bleaching of a resilient coral (Siderastrea stellata). (December 2021) - Barros, Yasmin; Lucas, Caroline Costa; Soares, Marcelo Oliveira
Abstract: We provide a baseline assessment of benthic cover, salinity, temperature, and bleaching in an urban intertidal reef. The cover is composed of a weedy coral ( Siderastrea stellata ), algae, and sand sediments. Fleshy macroalgae provided the most of the cover (23% to 43%), followed by coral (16% to 24%), and sediment (6% to 19%). Most of the tidal pools presented high algae cover with seasonal differences; whereas, the coral and sediment cover did not differ significantly over time. The bleached colonies ranged from 6% (November) to 76% (March) over the months according to the stress levels (warming and runoff). Temperature (30.3 to 33.5 °C), and salinity (35.2 to 43.2) characterized an extreme reef habitat. S. stellata resistance to chronic and acute stress makes it a bioindicator of environmental stress. The results highlight those marginal reefs may be simplified habitats, composed of monospecific coral populations and morphogically-simple macroalgae adapted to current pressures but its long-term survival is unlikely due to climate change. Highlights: Urban intertidal reefs are unique and understudied ecosystems. Benthic live cover is composed of a weedy disturbance-tolerant coral and fleshy macroalgae. Morphologically-simple and opportunistic algae provided the majority of the cover. Siderastrea stellata resistance to chronic stress makes it a bioindicator of environmental stress. These data provide baseline information for reef monitoring programs.